Spectroscopic families among diffuse interstellar bands - Wszołek, B. (Advances in Astronomy and Space Physics, 2012)
The inability to identify carriers of the diffuse interstellar bands (DIBs) is one of the longest standing problems in astronomy and astrochemistry. It is debated whether these carriers arise from dust or the gas component of the interstellar medium. Furthermore, different strength ratios of major DIBs along different lines of sight revealed many carriers responsible for DIBs origin. Any attempt to recognize these carriers must involve interdisciplinary collaboration between molecular physicists, chemists and astronomers. One expects that progress in this field will be possible when all known DIBs are divided into families in such a way that only one carrier is responsible for all bands belonging to a given family. Among all known DIBs we can see only few relatively strong bands and big number of rather weak ones. With better quality spectra one can expect to find more weak DIBs. It is very probable that DIBs originated by the same carrier have different intensities; in one spectroscopic family we expect to find stronger bands as well as weaker (and extremely weak) ones. Discovering new very weak DIBs may be therefore crucial when we want to find complete spectroscopic families among DIBs. Extracting spectroscopic families of DIBs is a task to be solved with usage of astronomical spectra of the best quality. After extracting any spectroscopic family, its carrier will be to find by the way of laboratory search supported by quantum chemical considerations. Analysing high resolution optical spectra of reddened stars we tried to find out the first true spectroscopic families among DIBs.